Teaching manuals in question: proposals for teaching the History of America (1971 and 2011) (Tempo e Argumento, 2021)
This article analyzes different proposals for teaching/learning contents on the history of America from two teaching manuals: Cadernos MEC: History of America (1971) and General History and Brazil (2011). The analysis is guided by the regressive method (BLOCH, 2001), in search of permanence and discontinuities in school subjetcs, in general, and History Teaching, in particular. Besides the forty-year interval between publications, the manuals distance themselves on pedagogical and historiographic aspects: Cadernos MEC: History of America varies between indications of New School ideas and a traditional perspective is linked to a traditional pedagogical perspective, with activities based on the mnemonic method; the didactic work of Vincentino and Dorigo (2011) consists of activities that favor the intellectual autonomy of students, which indicates an adaptation of the pedagogical content to neoliberal principles, by privileging the role of each student in their learning process. As for the conception of History, the 1971 manual presents positivist features, centered in dates and facts of characters from a predominantly political history. In the section pedagogical advisory of the 2011 work there are references with possible defeatist interpretations of the Spanish America, focusing on the exploration and violence of the "winners over the losers"; however, the exercises align with assumptions of the New History, which allows the elaboration of historical knowledge by students, through internal and external analysis of iconographic sources, the interpretation of historiographic texts, and the multiplicity of approaches and historical sources. Understanding which subjects take place in curricular expectations is a crucial choice for the composition of the tapestry to be woven by the historian (GINZBURG, 2007), but it also helps to think about the role of teaching manuals, such as the products they are, loaded with intentions.